DYNAMIC MODELLING OF S&P BSE SENSEX: EMPIRICAL EVIDENCE OF INFORMATION PERSISTENCE AND TRADING EFFECTS - SINGH, Dr. SHIKTA; DAS, Dr. CHANDRABHANU; Mishra, Dr. Padmaja (The journal of contemporary issues in business and government, 2022)
Purpose - The BSE Sensex, popularly known as SENSEX is considered as the pulse of domestic equity markets in India. However many researchers and policy makers also consider SENSEX as a barometer of Indian economy. The bull and bear phase of SENSEX is seen as upturn and downturn cycles in Indian perspective. The SENSEX consists of thirty well established stocks which are representative of various industrial sectors of Indian economy. Available literature provides evidence of attempt by many researchers in prediction and modelling of various market indices.Our study identifies a natural framework to study the dynamic structure of daily returns from BSE Sensex. The purpose of this study is to find evidence of index movement due to historical patterns or random shocks, which describe the economic environment under which the asset price is determined. Methodology - The study depended on daily returns from the market index collected from BSE website.The study sample was divided into two time zones. Five year period prior to recession was one time zone and the second time zone was five year period post recession. Auto regressive Moving average (ARMA) time series were applied to understand the dynamic structure of data. The research intends to find whether the effect of contemporary news and noise trading has a significant impact on market return. The paper further investigates has the effects changed after the global recession. Results- There was evidence of stationarity for log returns of the Sensex. It was observed that there is significant persistence to news or information affecting the returns in the form of under reaction. However the persistence has decreased after the global recession. Interestingly it was observed that the returns in both time zones were more guided due to disturbances or spread thus proving the evidence of frequent trading. Implications- Based on the findings, we were able to understand the dynamic structure of market returns and the coefficients governing the return series. The behaviour of index returns made us necessary to model the serial dependence.The slight decrease in persistence and trading effects suggests that investors are a bit cautious after the global recession. Since the effect is not much pronounced, this can be inferred that there has been no substantial change in market efficiency.